If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13x + 12 = 14x + 5 Reorder the terms: 12 + 13x = 14x + 5 Reorder the terms: 12 + 13x = 5 + 14x Solving 12 + 13x = 5 + 14x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14x' to each side of the equation. 12 + 13x + -14x = 5 + 14x + -14x Combine like terms: 13x + -14x = -1x 12 + -1x = 5 + 14x + -14x Combine like terms: 14x + -14x = 0 12 + -1x = 5 + 0 12 + -1x = 5 Add '-12' to each side of the equation. 12 + -12 + -1x = 5 + -12 Combine like terms: 12 + -12 = 0 0 + -1x = 5 + -12 -1x = 5 + -12 Combine like terms: 5 + -12 = -7 -1x = -7 Divide each side by '-1'. x = 7 Simplifying x = 7
| 5x-9=9x-4x | | -5x+3=-(x-33) | | 0.05z+0.2=0.15z+10.5 | | 15x-20x^2=0 | | -54=6n | | 7x^2-6x+5=0 | | 3+3u=-15 | | 2w^2-3w-65=0 | | x/4=-20+16 | | 4.5x+2x-9=17 | | 13-7x=168-42x | | 18-3(2.5)= | | 7x-5=21 | | 2c+6=6c-4 | | 20y^2-13y+2=0 | | 2=-1+-x | | 15z^2-4z-4=0 | | w^2+4w-45=0 | | =(5+(-8))x | | -3x+6(1/2)=-18 | | 2=-1+x | | 3(2y+5)=39 | | 8(w+1)-(-5w-2)=12w | | 3d^2-10d+7=0 | | x^2+1=145 | | =(4+(-7))x | | 1=2/3(-3)+b | | f(4)=-4-7+3 | | 1.5r-.5r=-5 | | x^2+1=45 | | -2=-6(5)+b | | 23l-l^2-90=0 |